2018
DOI: 10.1021/acs.jproteome.7b00811
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptidomics of the Rat Habenular Nuclei

Abstract: Conserved across vertebrates, the habenular nuclei are a pair of small symmetrical structures in the epithalamus. The nuclei functionally link the forebrain and midbrain by receiving input from and projecting to several brain regions. Each habenular nucleus comprises two major asymmetrical subnuclei, the medial and lateral habenula. These subnuclei are associated with different physiological processes and disorders, such as depression, nicotine addiction, and encoding aversive stimuli or omitting expected rewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 119 publications
0
13
0
Order By: Relevance
“…These processes include itch, learning, and reproduction; cardiovascular, gastrointestinal, and respiratory control; food and water intake; and analgesia and pain. 10 Neuropeptides are typically produced from the cleavage of larger precursor proteins, which is sometimes followed by enzymatic post-translational modifications (PTMs) such as Cterminal amidation, 11,12 acetylation, 13 phosphorylation, 14,15 sulfation, 16,17 and pyroglutamination. 18 Here liquid chromatography coupled to tandem mass spectrometry (LC−MS/MS) was used for the identification and quantification of neuropeptides.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These processes include itch, learning, and reproduction; cardiovascular, gastrointestinal, and respiratory control; food and water intake; and analgesia and pain. 10 Neuropeptides are typically produced from the cleavage of larger precursor proteins, which is sometimes followed by enzymatic post-translational modifications (PTMs) such as Cterminal amidation, 11,12 acetylation, 13 phosphorylation, 14,15 sulfation, 16,17 and pyroglutamination. 18 Here liquid chromatography coupled to tandem mass spectrometry (LC−MS/MS) was used for the identification and quantification of neuropeptides.…”
Section: ■ Introductionmentioning
confidence: 99%
“…1 e and g), which encode DCV contents such as substance P, neurokinin A, neuropeptide K, and neurokinin B 34 . In addition, a recent peptidogenomic study has reported MHb producing 262 neuropeptides generated from 27 prohormones, such as somatostatin (SST), neuropeptide Y (NPY), and secretogranin 1–3, etc 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Most of the input to the IPN are from the MHb 15 , 17 , and glutamatergic and cholinergic inputs from MHb project onto IPN neurons which are predominatly GABAergic 18 , 19 . The MHb also contains numerous neuropeptides such as tachykinins, VGF, neuropeptide Y, and secretogranin 1–3 20 , and CAPS2 is expressed in both MHbD and MHbV 5 , 6 , 21 . In this setting, CAPS2 may play a pivotal role in secretion of MHb neuropeptides.…”
Section: Introductionmentioning
confidence: 99%
“…To further take advantage of the abilities of HRAM mass analyzers, a systematic and comprehensive neuropeptidomic investigation of the rat habenular nuclei using LC-ESI Orbitrap, LC-ESI-FTICR, and MALDI-FTICR-MS was performed by the Sweedler Lab. They identified and localized 262 neuropeptides from 27 prohormones in the medial habenula region and 177 neuropeptides produced from 20 prohormones in the lateral habenula region to better understand interaction in the brain and the role of the habenular nuclei (Yang et al, 2018). These largescale studies can be very powerful in characterizing regions of the brain to find potential biomarkers for disease, although targeted approaches can be valuable as well.…”
Section: A Neuropeptides and Peptidesmentioning
confidence: 99%